2014
DOI: 10.1002/poc.3328
|View full text |Cite
|
Sign up to set email alerts
|

R. B. Woodward, A Great Physical Organic Chemist

Abstract: Robert Burns Woodward is considered one of the greatest synthetic organic chemists of our time, if not the greatest. This article presents evidence that Woodward was also one of the greatest physical organic chemists as well. Among Woodward and his collaborators' most important accomplishments in the field of physical organic chemistry are: the Woodward–Hoffmann rules; the derivation and use of structure–mechanism–reactivity relationships in his multifold structure determinations and total syntheses; the Woodw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 65 publications
(125 reference statements)
0
17
0
2
Order By: Relevance
“…In this instance, the ratio of citations of Woodward's Nobel Prize research to chemistry journals compared to life sciences journals is 1.5:1. Woodward was unquestionably an organic chemist whose influence on science has been on natural products structure determination (penicillin, strychnine), organic synthesis (quinine, strychnine, chlorophyll), and physical organic chemistry (the Woodward–Hoffmann rules, octant rule, Woodward–Fieser UV rules). It is seemingly surprising that so many life sciences’ publications cite Woodward's chemistry publications.…”
Section: Analysis Of the Disciplines Honored By The Nobel Prizes In Cmentioning
confidence: 99%
“…In this instance, the ratio of citations of Woodward's Nobel Prize research to chemistry journals compared to life sciences journals is 1.5:1. Woodward was unquestionably an organic chemist whose influence on science has been on natural products structure determination (penicillin, strychnine), organic synthesis (quinine, strychnine, chlorophyll), and physical organic chemistry (the Woodward–Hoffmann rules, octant rule, Woodward–Fieser UV rules). It is seemingly surprising that so many life sciences’ publications cite Woodward's chemistry publications.…”
Section: Analysis Of the Disciplines Honored By The Nobel Prizes In Cmentioning
confidence: 99%
“…Second, as indicated above,s everal instances were observed in which bibliographic analysis indicated amultitude of WoSresearch areas for the citations to the Nobel laureates seminal publications.O ne such example (Figure 3a nd Table SI-4) is that for the research honored by R. B. Wood-wards1965 Nobel Prize.Inthis instance,the ratio of citations of WoodwardsN obel Prize research to chemistry journals compared to life sciences journals is 1.5:1. Woodward was unquestionably an organic chemist whose influence on science has been on natural products structure determination (penicillin, strychnine), [15] organic synthesis (quinine,s trychnine,c hlorophyll), [39] and physical organic chemistry [40] (the Woodward-Hoffmann rules,o ctant rule,W oodward-Fieser UV rules). It is seemingly surprising that so many life sciences publications cite Woodwardsc hemistry publications.E xamination of those citing Woodwardsr eferences revealed that they are almost entirely chemical papers published in life science journals referring to Woodwards chemical papers.…”
Section: Analysis Of the Disciplines Honored By The Nobel Prizes In Cmentioning
confidence: 99%
“…Oddly enough, the formal underpinning of that mode of structure determination, disappearing in the 1950s, was to become the formal underpinning of retrosynthetic analysis (Figure B), appearing in the 1960s. Woodward's role in employing mechanistic thinking and quantum mechanical methods toward organic chemistry's most challenging problems was rapidly adopted by his colleagues worldwide.…”
Section: Introductionmentioning
confidence: 99%